Generation Z and Hoaxes: The Challenges of Media Education in the Digital Native Era - Agus Supriyanto; Gunawan Widjaja; Mowafg Masuwd (CV. Creative Tugu Pena, 2025)
This study examines the challenges of media education in addressing the spread of hoaxes among Generation Z, who are digital natives living in the digital era. Although Generation Z has extensive access to technology and social media, their levels of digital literacy vary significantly, particularly in information verification and digital ethics. Their susceptibility to hoaxes is influenced by the intensity of social media use, limited critical thinking skills, and the insufficient integration of media literacy into formal education. Using a literature review method, this study analyzes the characteristics of Generation Z, the factors contributing to their vulnerability to hoaxes, and effective strategies for strengthening media literacy. The findings highlight the need for comprehensive, collaborative, and adaptive media literacy education that aligns with technological developments and the specific characteristics of Generation Z, enabling them to become smart, critical, and responsible digital citizens. This study contributes to the understanding of how media education can be optimized to enhance Generation Z’s resilience against misinformation, offering a conceptual framework for developing more effective and contextually relevant media literacy programs